2014
DOI: 10.1037/a0036959
|View full text |Cite
|
Sign up to set email alerts
|

Test of mindfulness and hope components in a psychological intervention for women with cancer recurrence.

Abstract: Objective Psychological interventions can attenuate distress and enhance coping for those with an initial diagnosis of cancer, but there are few intervention options for individuals with cancer recurrence. To address this gap, we developed and tested a novel treatment combining Mindfulness, Hope Therapy, and biobehavioral components. Method An uncontrolled, repeated measures design was used. Women (N=32) with recurrent breast or gynecologic cancers were provided 20 treatment sessions in individual (n=12) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 86 publications
(128 reference statements)
1
50
0
1
Order By: Relevance
“…generating workable routes to important goals) and agency thinking (i.e. generating and maintaining goal-relevant momentum and motivation) (Cheavens, Feldman, Gum, Michael, & Snyder, 2006;Feldman & Dreher, 2012;Thornton et al, 2014). An example of a group activity that is drawn from Hope Therapy is the 'goal maps' activity (Cheavens et al, 2006).…”
Section: Agency and Values In The Self-regulation Of Behaviormentioning
confidence: 99%
“…generating workable routes to important goals) and agency thinking (i.e. generating and maintaining goal-relevant momentum and motivation) (Cheavens, Feldman, Gum, Michael, & Snyder, 2006;Feldman & Dreher, 2012;Thornton et al, 2014). An example of a group activity that is drawn from Hope Therapy is the 'goal maps' activity (Cheavens et al, 2006).…”
Section: Agency and Values In The Self-regulation Of Behaviormentioning
confidence: 99%
“…20 Counseling differs from advice and assumes not doing something to the patient, but doing something with the patient. Consisting of science and art, it aims to improve the clinical prowess of therapists, proposing, as in the Watsonian theory, a change in the patterns of unideretional communication, centered in the figure of the therapist.…”
mentioning
confidence: 99%
“…21 Qualitative studies in women with relapsed cancer reported a multiplicity of thoughts and feelings related to the physical symptoms of the disease, numerous chemotherapy sessions, past memories and concerns about the future. 35 The practice of Mindfulness in this context presents itself as an effective psychological intervention in improving oncological coping patterns 20 and for relieving suffering in other conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations